Short-term clinical efficacy of five-step manipulation under anaesthesia combined with arthroscopic shoulder surgery for adhesive capsulitis - Zeng, Weiqing; Jin, Ziqi; Li, Hongmei; Zhou, Liangji; Tan, Yongxing; Chai, Sheng; Lü, Qing; Wei, Hua; Tang, Gangjian (Frontiers in Surgery, 2026)
ObjectiveTo compare the short-term efficacy of arthroscopic capsular release combined with five-step manipulation under anaesthesia vs. five-step manipulation under anaesthesia alone for adhesive capsulitis.MethodsThis retrospective study included 66 patients assigned to arthroscopic capsular release (ACR) plus five-step manipulation under anaesthesia (MUA) (n = 31) or five-step MUA alone (n = 35); both cohorts received intra-articular “cocktail” irrigation. Outcome assessments comprised American Shoulder and Elbow Surgeons (ASES) scores and Visual Analogue Scale (VAS) pain scores at 1 week, 1 month, and 6 months post-operatively; peri-operative metrics included operative time, length of post-operative hospital stay, and total hospitalisation cost.ResultsOne week and one month post-operatively, VAS scores in the two groups were similar (P > 0.05). At 6 months, the treatment group exhibited significantly lower VAS scores than the control group (1.83 ± 0.70 vs. 2.55 ± 0.56, 95% CI: −1.03 to −0.41, P < 0.001). ASES scores did not differ between groups at 1 week or 1 month (P > 0.05), but were significantly higher in the treatment group at 6 months (76.68 ± 6.67 vs. 73.43 ± 2.54, 95% CI: 1.42–5.32, P = 0.009). No complications occurred in either group. Operative time, postoperative hospitalisation days and hospitalisation cost were higher in the treatment group (P < 0.05).ConclusionCompared with simple five-step MUA, the combination therapy of five-step MUA and ACR provides superior pain relief and higher ASES functional scores at 6 months after surgery. However, operation time, postoperative hospitalisation days and hospitalisation costs correspondingly increase. Due to the small sample size and short clinical observation time, further follow-up is needed for long-term efficacy.